Prioritizing Drug Procurement Using ABC, VEN, EOQ And ROP Combination - Susilo Romadhon; Retantyo Wardoyo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2021)
The availability of drugs is one of the things that must be considered because if there is a deficiency or excess it can cause loss or disruption in patient care. The process to procure drugs that are still being carried out with uncertain considerations will create scheduling irregularities, this will have an impact on inventory costs due to accumulated inventory in warehouses or the absence of these drugs.This study aims to produce a decision support system for drug procurement using a combination of ABC methods, VEN analysis, ROP and EOQ.The test results show that the system can provide 3 recommendations for decision makers with consideration of the results of the ABC and VEN matrices and procurement calculations based on EOQ and ROP. The result of calculating the total Inventory Cost in the case example of the orodine drug based on the pharmacy calculation is IDR 708,500 while the calculation using the Economic Order Quantity method is IDR 689,381 from the calculation results obtained a savings of IDR 19,119.